Direct experimental determination of spectral densities of molecular complexes (2014)
Determining the spectral density of a molecular system immersed in a proteomic scaffold and in contact to a solvent is a fundamental challenge in the coarse-grained description of, e.g., electron and energy transfer dynamics. Once the spectral density is characterized, all the time scales are captured and no artificial separation between fast and slow processes need to be invoked. Based on the fluorescence Stokes shift function, we utilize a simple and robust strategy to extract the spectral density of a number of molecular complexes from available experimental data. Specifically, we show that experimental data for dye molecules in several solvents, amino acid proteins in water, and some photochemical systems (e.g., rhodopsin and green fluorescence proteins), are well described by a three-parameter family of sub-ohmic spectral densities that are characterized by a fast.